Techno-economic assessment of on-farm anaerobic digestion system using attached-biofilm reactor in the dairy industry - Tan, Jia Boh; Jamali, Nur Syakina; Tan, Wei En; Che Man, Hasfalina; Zainal Abidin, Zurina (MDPI AG, 2021)
In this study, a techno-economic assessment of an on-farm biogas system using an anaerobic biofilm reactor utilizing cow manure as a fermentation substrate was evaluated. A projection model was developed using Microsoft Excel software with three outputs, the size and dimension of a bioreactor, experimental microbial kinetic studies, and the economic studies based on the experimental results. Characterization analysis of cow manure wastewater showed the total solid (TS), total volatile solid (TVS), total carbohydrate (TC), chemical oxygen demand (COD), and pH values which were 10.95 g/L, 8.65 g/L, 6.65 g/L, 57.80 g/L, and 7, respectively. Using the modified Gompertz equation for the microbial studies, it was found that, at 37 °C and 20 days hydraulic retention time (HRT), the biogas yield was 934.54 mL/gVS, the volume of biogas produced was 11.28 m3/d, and 22.56 kWh of electricity was generated. The Gompertz prediction helps to determine the optimal HRT for the system so that the microorganisms are at their optimum stage to produce biogas. The economic analysis was done, and the results illustrated that, when the rate of cow manure produced was at 55 L/day.cow, the net present value (NPV) was RM 611,936.09, with a 13% internal rate of return (IRR), 0.14 return on investment (ROI), and 7.02 years of payback period (PP). By developing a techno-economic assessment that included all the necessary parameters such as sizing of the bioreactor, microbial kinetic studies, and economics of the plant, farmers could easily implement the system into their farms. This model showed that the anaerobic digestion system utilizing an attached biofilm with cow manure as a fermentation inoculum and substrate was applicable on an industrial scale to generate electricity and reutilize to the farm, at the same time generating additional income from the production of fertilizer.